ANALISA VALUE ENGINEERING PADA PROYEK GEDUNG RISET DAN MUSEUM ENERGI DAN MINERAL INSTITUT TEKNOLOGI BANDUNG - NUR ASTY PRATIWI (Jurnal Teknik Sipil dan Lingkungan, 2014)
One of analysis method that used to evaluate the construction project planning is value engineering. The purpose of value engineering are cost saving, performance optimization, and the efficiency of the time, but still consider the function, quality, and aesthetic of the project. The main reason for using this analysis method is a systematic and procedural approach in the object evaluation. The value engineering stages are information, creative (speculation), analysis, recommendation (planning or development), and presentation. Value engineering analysis begins by selecting one of the activities that have a higher cost than any other activity, then analysis to determine alternative classification of works or materials with basic and secondary functions according to the requirements in order to obtain a better cost. In this value engineering analysis, steel deck system selected as a replacement for the conventional concrete slab construction. Steel deck system’s product that used in this project is Union Floor Deck W-1000. Union Floor Deck W-1000 has double function. There are permanent formwork and positive reinforcement. Steel rebar in tension can be reduced or even could be replaced totally by Union Floor Deck W-1000. Fast and easy installation for concrete or steel construction generally. It differs from conventional formwork which is to be installed span by span, Union Floor Deck W-1000 can be used as multiple span for faster installation. The results of this value engineering analysis that uses Union Floor Deck W-1000 as an alternative replacement from conventional concrete slab is cost saving until Rp 120.988.335,12 or 9,297 % of total job cost budget from floor plates prior to value engineering analysis. Key Words : Value Engineering, Cost Saving, Cost